The impact of auditor education level on the relationship between auditor busyness and audit quality in Turkey - Murat Ocak (Cogent Business & Management, 2018)
In this study, I examine the effect of auditor education level on the relationship between auditor busyness and audit quality using Turkish listed firms. Prior studies regarding auditor busyness have not considered how auditor busyness affects audit quality in the case of auditors who are less educated or more educated. I created some interaction variables using busyness and auditor education level. Additionally, the sample was split into two groups based on auditor education level. The main estimation results show that auditor busyness (auditor education level) negatively (positively) affects audit quality. Auditor formal education level minimises the negative effect of auditor busyness on auditor quality. Also, I found that the negative effect of auditor busyness on audit quality is more pronounced in the case of less educated auditors.
Keywords: 650